Image and Memory in Medieval Germany: Sigebert of Minden and his Sacramentary (1022-1036) - Rodríguez Viejo, Jesús (Mirator, 2025)
This article explores the decoration, perception, and function of the Sigebert Sacramentary (Berlin, Staatsbibliothek, MS. Theol. lat. fol. 2) one of the largest and most luxurious, yet overlooked manuscripts ever created in medieval Central Europe and manufactured at the Abbey of St Gallen in the 1020s as part of a group of eight liturgical manuscripts. The contribution analyses in particular the ecclesiastical symbolism of the unique scenes in this manuscript and offers a contextualisation for its commission by the ambitious bishop Sigebert of Minden (1022-1036).